Accumulation, Composition, Density, and Volume of Marine Litter on Palu Bay - Hermawan, Roni; Hasanah, Nur; Nurdin, Muhamad Saleh; Eka Putra, Aswad; Tis'in, Musayyadah; Riza, Femi; Mangintung, Septina Fifi; Rukka, Andi Heryanti; Purwanto, Eko; Ramadhani, Nurul Rizki; Nursalwa, Nursalwa; Darae, Charlos Daniel; et al. (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
Marine litter poses an increasing threat to the coastal ecosystem of Palu Bay, Indonesia, driven by contrasting land-based human activities. This study assessed the accumulation, composition, density, and volume of macro-debris (>2.5 cm) at four coastal stations representing residential, river-influenced, and tourism-dominated areas. Surveys were conducted from June to September 2025 using a line transect method. The results showed marked spatial differences in marine litter characteristics. Residential and river-influenced sites (Baiya and Mamboro Beaches) recorded the highest debris weights (4003.67–4378.22 g/m²), dominated by heavier household waste transported via river systems. In contrast, tourism areas (Taman Ria and Kampung Nelayan Beaches) exhibited lower debris weights (1697.67–1892.37 g/m²) but significantly higher item densities (14.46–17.28 items/m²) and volumes, reflecting the dominance of lightweight, single-use plastics from recreational activities. Plastic debris dominated all stations, exceeding 94% in tourism zones. These findings demonstrate a clear dichotomy in litter sources and characteristics between tourism and residential areas, underscoring the need for targeted management strategies. Effective mitigation should prioritize single-use plastic restrictions, adequate waste facilities, and visitor awareness in tourism areas, alongside improved household waste collection and riverine waste control in residential watersheds. Such source-specific approaches are essential for sustainable coastal management in Palu Bay and comparable semi-enclosed bays.